Lateral parabrachial nucleus and serotonergic mechanisms in the control of salt appetite in rats - Menani, José Vanderlei [UNESP]; Thunhorst, R. L.; Johnson, A. K. (Amer Physiological Soc, 1996)
This study investigated the effects of bilateral injections of serotonergic receptor agonist and antagonist into the lateral parabrachial nucleus (LPBN) on the ingestion of water and 0.3 M NaCl induced by intracerebroventricular angiotensin II (ANG II) or by combined subcutaneous injections of the diuretic furosemide (Furo) and the angiotensin-converting enzyme inhibitor captopril (Cap). Rats had stainless steel cannulas implanted bilaterally into the LPBN and into the left lateral ventricle. Bilateral LPBN pretreatment with the serotonergic 5-HT1/5-HT2 receptor antagonist methysergide (4 mu g/200 nl each site) increased 0.3 M NaCl and water intakes induced by intracerebroventricular ANG II (50 ng/mu l) and 0.3 M NaCl intake induced by subcutaneous Furo + Cap. Pretreatment with bilateral LPBN injections of a serotonergic 5-HT2A/2C receptor agonist DOI (5 mu g/200 nl) significantly reduced 0.3 M NaCl intake induced by subcutaneous Furo + Cap. Pretreatment with methysergide or DOI into the LPBN produced no significant changes in the water intake induced by subcutaneous Furo + Cap. These results suggest that serotonergic mechanisms associated with the LPBN may have inhibitory roles in water and sodium ingestion in rats.
Keywords: angiotensin II; water intake; salt intake; furosemide; sodium chloride intake